Multiple signaling pathways in the frontiers of lung cancer progression - Liu, Hao; Zhou, Dujuan; Ou, Yangjing; Chen, Shuanghua; Long, Yunzhu; Yuan, Ting; Li, Yukun; Tan, Yingzheng (Frontiers in Immunology, 2025)
Lung cancer is a prevalent malignant tumor and the leading cause of cancer-related mortality worldwide. LC is a complex respiratory condition that poses significant challenges for both clinicians and researchers. Crucially, dysregulation of molecular signaling pathways is a key message point in LC. Numerous reviews have highlighted effective treatments for LC by targeting disrupted signaling pathways. Understanding the roles and interconnections of various signaling pathways in LC is crucial. Therefore, this paper reviews the pathogenesis, biological functions and their important interactions in lung cancer. Frist, we reviewed relevant signaling pathways involved in LC, including Wnt, PI3K/Akt, Notch, PD-1/PD-L1, NF-κB, Hippo, MAPK, Hedgehog, AMPK. Immediately thereafter, we further explored the biological functions of LC in this area of pathophysiology, such as apoptosis, metastasis and proliferation. In conclusion, after our deeper understanding of the interactions of these signaling pathways in LC. And we must recognize that the interactions between the above signaling pathways can lead to comprehensive as well as novel therapeutic approaches for LC.